The potential of using forest residue to offset coal use in co-fired coal power plants in the eastern United States - Parent, Jason; Graziano, Marcello; Yang, Xiusheng (Harrison) (International Journal of Agricultural and Biological Engineering, 2014)
Abstract: The global transition from fossil fuel-based energy sources to renewable energy sources will be most effective, for at least the near future, by utilizing local resources and existing infrastructure. In many areas of the eastern United States, forest residue is abundant and can be used in existing facilities to supplement coal in coal-fired power plants. Thus forest residue has potential as a renewable energy source that could be effectively utilized in the near future. This study uses GIS to estimate the potential quantity of forest residue available for use in coal-fired power plants in the eastern United States. Transportation costs limit the distance over which it is feasible to transport forest residue to the power plants and these costs may fluctuate depending on economic conditions. Thus, we consider three scenarios in our analysis assuming the maximum feasible transport distances to be 60, 80, and 100 km. In the eastern U.S., the total annual forest residue available to coal plants is approximately 29.4, 40.2, and 48.2 million dry tons, respectively, for maximum transport distances of 60, 80, and 100 km. Assuming an 80 km transport distance, forest residue has the potential to reduce coal consumption by 22.3 million tons per year. Under this scenario, greenhouse gas emissions would be reduced by almost 58.1 million tons per year, and NOx and SOx emissions would be reduced by 69.3 and 122.6 thousand tons respectively. This analysis suggests that by offsetting coal use, forest residue has the potential to substantially reduce power plant emissions. Keywords: forest residue, coal, biofuel, co-firing, GIS, alternative energy DOI: 10.3965/j.ijabe.20140704.011 Citation: Parent J, Graziano M, Yang X S. The potential of using forest residue to offset coal use in co-fired coal power plants in the eastern United States. Int J Agric & Biol Eng, 2014; 7(4): 99－105.